2017
DOI: 10.1038/srep46217
|View full text |Cite
|
Sign up to set email alerts
|

Male Dispersal Pattern in Golden Snub-nosed Monkey (Rhinopithecus roxellana) in Qinling Mountains and its Conservation Implication

Abstract: Golden snub-nosed monkey (Rhinopithecus roxellana) is one of the most endangered primate species found in China, exhibiting multilevel society consisting of several one-male-females together with their offspring units (OMU), and all-male units (AMU). Female dispersal patterns of the species within herd have been well documented, whereas those of the males within or between herds are still poorly understood. Our results based a long-term observation indicate that more than half of sub-adult males, and half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The daily path length varies from 0.75 to 5 km with a mean of 2.1 km (Tan et al, ). R. roxellana has a male‐based dispersal system (Chang et al, ; Huang et al, ). We parameterized our models of refugia according to those values; for example, patch areas had to be >7.4 km 2 , and the distance to the nearest patch had to be <2.1 km and located in a protected area for more effective management and protection.…”
Section: Methodsmentioning
confidence: 99%
“…The daily path length varies from 0.75 to 5 km with a mean of 2.1 km (Tan et al, ). R. roxellana has a male‐based dispersal system (Chang et al, ; Huang et al, ). We parameterized our models of refugia according to those values; for example, patch areas had to be >7.4 km 2 , and the distance to the nearest patch had to be <2.1 km and located in a protected area for more effective management and protection.…”
Section: Methodsmentioning
confidence: 99%
“…While previous studies of some primates with multilevel societies noted the absence of such an ability or motivation (Bergman 2010 ; Maciej et al 2013 ), studies of R. roxellana have shown that the social units of a group coordinate their activities on a daily basis (Liu et al 2016 ; Wada et al 2015 ; Zhang et al 2010 ) and that the animals engage in particularly significant interactive events among units (Qi et al 2017 ). For example, the resident males have been observed to collectively defend their OMUs against the bachelor males of the AMU (Huang et al 2017 ; Xiang et al 2014 ). The adult females of an OMU copulate with the males of other units and sire offspring (Guo et al 2010 ; Zhao et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, based on the source-filter theory, we investigated the individuality in coo calls of adult male R. roxellana . We chose adult males as our study subjects, because they play an important role in the maintenance of social cohesion and spacing at both levels within and between units (Huang et al 2017 ; Qi et al 2017 ; Xiang et al 2014 ). We first examined whether coo calls had a sufficient degree of individual distinctiveness that would permit discrimination among callers.…”
Section: Introductionmentioning
confidence: 99%
“…OMUs do not avoid each other, but move, forage and rest together to form a breeding band 17 . Young male normally emigrate from their natal groups before sexual maturity, and form all male units, several of which coalesce into an all male band (AMB) 18 , 19 . All male band follows around the breeding band, all together comprising a herd 18 .…”
Section: Methodsmentioning
confidence: 99%